Diversity and abundance of orchids in Crocker Range Park, Sabah, Malaysia - Hamelda Francisca Majit; Monica Suleiman; Rimi Repin (Penerbit UMS, 2011)
A study on the diversity of orchids was carried out in Crocker Range Park, Sabah, Malaysia. Twenty seven plots of 50 m x 10 m each were set up in three different forest types. Four environmental parameters, namely temperature, humidity, altitude and canopy cover were measured to determine their influence on the occurrence and diversity of orchids. A total of 149 species belonging to 33 genera were recorded. Old secondary forests had the most diverse orchid species compared to young secondary forests and primary forests. The number of individuals and species were significantly correlated (p4.004, p4.001) with altitude while humidity, temperature and canopy did not influence the species composition.